(untitled) (Medical Forum Monthly, 2024)
Aim: The aim of this study was to determine the presence of pesticide residues organophosphate and pyrethroid in the milk of women and in serum of breast cancer patients from different localities of Karachi due to pesticide exposure. Study Design: An experimental study. Place and Duration of Study: This is a research-based study that was conducted in the Department of Pharmacology, Institute of Pharmaceutical Sciences, Baqai Medical University, Karachi from March 2008 to March 2010. Materials and Methods: A total 40 milk samples were collected from private clinics and 6 serum samples from breast cancer patients were also collected from private cancer hospitals based at different areas of Karachi. All the samples were analyzed for the presence of pesticide residues. Samples of milk and serum were prepared accordingly and the purified samples were injected into the HPLC apparatus. The peaks of the samples were compared by the retention time of the standard peaks. The chromatogram obtained indicated the quantity of pesticide residues. Results: Milk samples and serum samples were analyzed using HPLC technique. Pesticides such as malathion, permethrin, deltamethrin and Polytrin-C were detected in different concentrations. The levels were significantly higher than the maximum residual limit. Conclusion: It is concluded that the presence of pesticides in the human body is a major concern in the development of various ailments because of possible immunotoxic, mutagenic and carcinogenic potential of pesticides.